Effect of macroeconomic variables volatilities on firms profitability: Analysis of listed firms on the Ghana stock exchange - CRABBE, DAVID (KNUST, 2025)
A Thesis Submitted In Partial Fulfillment Of The Requirement For The Degree Of Master Of Science Finance And Investment.